Diversity of sunflower rust pathogen biotypes (Puccinia helianthi Schwein.) in the Rostov region - E. S. Lepeshko (Зерновое хозяйство России, 2024)
In the last decade there has been established an increase in the prevalence of Puccinia helianthi in sunflower crops in Russia. In the Rostov region, on the territory of the Don Experimental Station (the Azov region), severe damage by the sunflower rust pathogen was established in 2020. In this regard, there was a need to study the race of the fungus on sunflower crops in the Rostov region. The purpose of the study was to identify rust pathogen isolates collected from sunflower crops in accordance with the accepted international triplet nomenclature in different areas of the Rostov region in the period 2021–2023. As testers, there was used a set of differentiating lines of sunflower resistance to the pathogen, containing SM 90, SM 29, P-386, HA-R1, HA-R2, HA-R3, HA-R4, HA-R5 and the line ‘ED 47’, susceptible to all biotypes of the fungus. The total sample consisted of 237 parasite urediniospore isolates collected from infected leaves of sunflower plants. There were differentiated 34 biotypes of P. helianthi. The most virulent pathotype 777 was identified among isolates from the Tatsinsky, Morozovsky and Konstantinovsky districts of the region in 2023. The race with code number 700 was identified in almost all represented areas of the region and accounted for 52.7% of the studied sample of sunflower rust pathogen isolates. In the current work the racial composition of the pathogen in the Rostov region was studied for the first time. The study results have indicated the need to continue monitoring new biotypes of P. helianthi, as well as expand and accelerate work on the development of sunflower hybrids resistant to the predominant race with code 700 in the sample.